Radiology and clinical prognosis of posterior malleolar fractures with different Step-off levels - Yongqi Li; Rui Luo; Bing Li; Hongzi Wu; Zongbiao Bai; Yong Jin; Yunfeng Yang (BMC Musculoskeletal Disorders)
Abstract Objective Ankle fracture involving the posterior malleolus is characterized by poor prognosis, and its risk factors remain controversial. This study aims to evaluate the influence of posterior malleolar fractures with different step-off levels on posttraumatic osteoarthritis and functional prognosis and identify the related risk factors that affect the clinical prognosis of posterior malleolar fractures. Methods The information of 134 patients with ankle fractures involving the posterior malleolus from January 2016 to December 2021 was retrospectively collected. The patients’ posterior malleolar fracture reduction quality, fracture healing status, and severity of ankle posttraumatic osteoarthritis (Kellgren–Lawrence scale) were evaluated by radiology, and the ankle function was assessed using Olerud-Molander score, visual analogue scale (VAS) score, and range of ankle motion. Results All 134 patients achieved fracture healing, with an average follow-up period of 42 (13,78) months. Thirty-nine patients (29%) showed positive ankle posttraumatic osteoarthritis. The average Olerud-Molander score was 89.9 (70,100), the average VAS score was 1.0 (0,5), and the ankle dorsiflexion restriction was 4.0° (0°,9°) on the average. Compared with the proportion of patients with postoperative step-off of < 1 mm of posterior malleolar fracture, the proportion of patients with positive posttraumatic osteoarthritis at postoperative step-offs of 1–2 and > 2 mm was higher (P < 0.05), and the functions of the affected limbs were evidently degraded Olerud-Molander score, VAS score, and ankle dorsiflexion restriction; P < 0.05). However, the differences in the proportion of patients with positive posttraumatic osteoarthritis and functional prognosis between postoperative step-offs of 1–2 mm and > 2 mm were not statistically significant (P > 0.05). Posterior malleolar step-off was an independent, statistically significant risk factor for posttraumatic osteoarthritis (Wald = 14.23, P < 0.01), and both posterior malleolar step-off and posttraumatic osteoarthritis were independent risk factors that led to the poor functional prognosis (P < 0.05). Conclusion Clinically, importance should be given to the anatomical reduction of posterior malleolar fractures and the incidence of posttraumatic osteoarthritis to improve the long-term functional effects on affected limbs. Fund program Natural Science Foundation of Xinjiang Uygur Autonomous Region（2024D01C11; Xinjiang Tianshan Talent Training Program (2023TSYCJC0053); Shanghai Science and Technology Commission Project (22S31900300, 21ZR1458500).